2015
DOI: 10.1055/s-0035-1566155
|View full text |Cite
|
Sign up to set email alerts
|

Vibrant Soundbridge and Bone Conduction Hearing Aid in Patients with Bilateral Malformation of External Ear

Abstract: Introduction Hearing loss is the most common clinical finding in patients with malformation of the external ear canal. Among the possibilities of treatment, there is the adaptation of hearing aids by bone conduction and the adaptation of implantable hearing aids. Objective To assess speech perception with the use of Vibrant Soundbridge (VBS - MED-EL, Innsbruck, Austria) associated with additional amplification in patients with bilateral craniofacial malformation. Method We evaluated 11 patients with bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Still regarding the condition of speech in silence, a study that analyzed a sample of 11 individuals, over 12 years of age and with bilateral ear malformation, found no significant differences with the individual use of the Vibrant Sound Bridge × conventional and Vibrant Sound Bridge × Softband (18) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Still regarding the condition of speech in silence, a study that analyzed a sample of 11 individuals, over 12 years of age and with bilateral ear malformation, found no significant differences with the individual use of the Vibrant Sound Bridge × conventional and Vibrant Sound Bridge × Softband (18) .…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the speech recognition in noise, previous studies, found results compatible with the data presented in the present study. (18,(20)(21)(22)(23)(24)(25) These results, despite showing small benefits with the use of sound amplification, have limitations such as the reduced sample, a fact that may be associated with the prevalence of atresia, which is estimated at 1 in 10,000 births, making it difficult to find subjects affected by the anomaly. (26) However, other studies in this area have also shown a reduced sample (16,26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…A casuística deste estudo foi composta por 20 indivíduos, sendo 10 normo-ouvintes e 10 usuários de VSB com atresia de orelha bilateral e perda auditiva (G1). Comparando com outros estudos sobre o tema, este número não pode ser considerado pequeno, visto que a maioria dos trabalhos foi realizada com estudo de caso e casuísticas compostas por até 12 indivíduos Kiefer et al, 2006;Frenzel et al, 2009;Nicollas;Bernadeschi et al;Colletti et al, 2011; Stankeviciute; Petrulionis; Sarasty, 2012;Pujol;Zernotti et al, 2013;Yang et al, 2014;Mondelli et al;Zhao et al, 2016;Célérier et al;Leinung et al, 2017). Além de ser o primeiro estudo realizado com o objetivo proposto nesta população, os participantes do G1 apresentaram atresia de orelha bilateral, o que deve ser considerado, visto que a maior parte dos casos de atresia de orelha é unilateral (Schuknecht, 1989;Jovankovičová et al, 2015).…”
Section: Discussionunclassified
“…Resultados semelhantes foram encontrados por outros estudos Kiefer;Arnold;Staudenmaier 2006;Frenzel et al, 2009;Nicollas;Bernadeschi et al;Colletti et al, 2011; Lesinskas; Stankeviciute; Petrulionis; Sarasty, 2012;Pujol;Zernotti et al, 2013;McKinnon et al;Yang et al, 2014;Ernst et al;Mondelli et al;Zhao et al, 2016;Célérier et al;Leinung et al, 2017).…”
Section: Audibilidade Alcançada Com O Uso Do Vsbunclassified
See 1 more Smart Citation